2020
DOI: 10.2196/15460
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Apps to Support Falls Rehabilitation Exercise: App Development and Usability and Acceptability Study

Abstract: Background Falls have implications for older adults’ health and well-being. Strength and balance interventions significantly reduce the risk of falls. However, patients do not always perform the unsupervised home exercise needed for fall reduction. Objective This study aims to develop motivational smartphone apps co-designed with health professionals and older adults to support patients to perform exercise proven to aid fall reduction and to explore the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 48 publications
0
62
0
Order By: Relevance
“…Insufficient attention has been paid to the clinical assessment of the hand function skills needed to operate technology-based devices such as tablets and smartphones, especially the fine motor skills needed to interact with a touchscreen interface. Such data are of particular importance to determine the extent to which older adults are able to cope with the use of such devices that support an active lifestyle by increasing physical exercise, decreasing social isolation, supporting social communication, and increasing participation in meaningful occupations [ 10 , 11 ]. Usage of these devices may enhance the cognitive and physical performance of community-dwelling older adults and provide monitoring technologies in order to increase their independence, autonomy, quality of life, security [ 12 , 13 , 14 ] and improve their medical management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient attention has been paid to the clinical assessment of the hand function skills needed to operate technology-based devices such as tablets and smartphones, especially the fine motor skills needed to interact with a touchscreen interface. Such data are of particular importance to determine the extent to which older adults are able to cope with the use of such devices that support an active lifestyle by increasing physical exercise, decreasing social isolation, supporting social communication, and increasing participation in meaningful occupations [ 10 , 11 ]. Usage of these devices may enhance the cognitive and physical performance of community-dwelling older adults and provide monitoring technologies in order to increase their independence, autonomy, quality of life, security [ 12 , 13 , 14 ] and improve their medical management [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographics of the older adults and health professionals in the workshops are reported in more depth in a previous study [ 33 ]. We recruited 5 health professionals, including 2 physiotherapists, 1 OT, 1 rehabilitation assistant, and 1 assistant practitioner.…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 of the patients already had Wi-Fi, and 1 agreed to let us install Wi-Fi to enable them to use teleconferencing. A total of 11 health professionals took part in the focus groups; 8 were women, 9 were physiotherapists, 1 was a nurse, and 1 was an OT (see the study by Hawley-Hague et al [ 33 ] for further demographics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have strived to integrate technology into physical exercise programs that were revealed as effective for adherence and overcoming barriers to exercise, as well as for improvements in health and independence [19]. Currently, several technological solutions address specific aspects of the fall cycle; however, the majority of these do not address fall detection, fall risk assessment, and fall prevention simultaneously.…”
Section: Introductionmentioning
confidence: 99%